(untitled) (Jurnal Pilar Nusa Mandiri, 2014)
This study has the purpose to implement an object-first approach to students who have not studied structured programming with structured programming that has been studied. Samples from this study were students totaling 48 students, which consisted of 24 students learn and understand the concepts of OOP without Object-First approach and 24 other students using Object-First approach. Data were analyzed using t-test prior to testing the validity, reliability, normality and homogeneity test. From the research results found in the study java programming with Object-First approach has not been proven to facilitate the understanding and studying the concepts of OOP, ie there is no difference between without using Object-First approach using Object-First approach is evident from the (t count (1,927) <t table (<2.012)) and the ratio of the mean value of the pretest (61.33) is higher than the posttest (56.54).